MINERALOGICAL INVESTIGATIONS OF EXPERIMENTALLY SHOCKED DOLOMITE: IMPLICATIONS FOR THE OUTGASSING OF CARBONATES - Skála R.; Ederová J.; Matějka P.; Hörz F. (My University, 2002)
The response of carbonate-bearing sediments to transient shock waves is important in understanding atmospheric CO(2) pollution caused by large-scale impacts on Earth. As a consequence, we examined polycrystalline dolomite that was experimentally shocked to pressures from 4.6 to 68.0 GPa. Electron microprobe data, at spatial resolutions of 3-5 fun, do not reveal any decomposition products of dolomite. XRD and micro-Raman spectroscopy show distinct broadening of reflections and spectral bands, respectively, with increasing peak shock pressure. The substantial scatter in the bandwidth of the Raman spectra demonstrates considerable localization of shock-induced damage on scales of similar to10-20 mum. XRD patterns reveal the presence of small quantities of MgO and calcite at pressures >60 GPa; these phases must be very fine grained (<1 mum), because they could not be resolved via microprobe. These observations suggest that dolomite decomposition begins at pressures just above 60 GPa, but it remains a relatively minor effect at even 68 GPa. However, massive outgassing occurs at slightly higher (>70 GPa) pressures, as inferred from the characteristic and reproducible failure of the metallic containers that house the dolomite target during these shock experiments. Identical containers housing volatile-free silicates routinely survive shocks as high as 90 GPa. These relatively high threshold pressures for the outgassing of dolomite are consistent with recent experimental and theoretical efforts by a number of groups on the shock behavior of calcite. Cumulatively, these developments imply that the total amount of CO(2) released during the Cretaceous-Tertiary event could be considerably smaller than previously estimated.